Improving speaking skill with the help of modern technologies - Sattarova Soadat Narzullayeva; Muqumova Nafisa Qarshi qizi (Zien Journals, 2021)
Technology tools are seen as ways to help student improve language skills such as speaking skills. Internet, podcast, video conferencing is the best tool to teach speaking skills. Speaking is one of the skills that students need to acquire when learning English. Speech is an important means of communication. Additionally, this article is about ways of speaking skill with technology
Keywords: Speaking; ICT; enhance speaking; EAL